The Creation Motif in the Book of Job - Forrest, William Edward Robert (My University, 1975)
The Hebrew version of Job (BH³) is the authoritative text in this investigation of the creation motif in the book. Although the authenticity of the many textual and other problems with which this book is replete is not disputed, nevertheless it is legitimate to treat the work as a unit since it has existed as such for many generations. The proper appreciation at the role and significance of the creation motif in Job provides a convincing explanation of the book taken as a whole.
The nature of the creation motif in Job is complex. It include notions of kingship, temple-building, conflict with chaos and with mythological monsters. These ancient Near Eastern notions of creation are adapted in this book to meet Hebrew requirements. The motif as it appears in Job also contains reflections on Genesis 1 and 2 and on other sources or creation thought in the Bible. The essence of the motif is the relationship of God to man in creation. It is this relationship which provides the subject matter for the poet's speculation.
The function of the creation motif in Job is to assert the poet's belief in the potency and significance of the divine self-disclosure in the realm of creation. Job, who is deprived at all that could then be expected to make life tolerable, is also robbed of the comforts contained in the proper observance at conventional morality and correct religious behaviour. The source of true religion is the fulfilment of the Law, as the friend repeatedly assert. Because Job suffers the friends assume that he has sinned. But Job is convinced that he has not transgressed the Law. Consequently, he is forced to look elsewhere for an explanation of his adversity. His search eventually meets with success when Yahweh reveals himself to Job in the final scenes of the book. In them Job's relationship to God is restored. He recognizes his part in the divinely ordered creation. Job's belief that it is possible to know God outside the pale of the Law is vindicated. Creation provides the milieu for that knowledge. However, as the terms of the theophany indicate, that knowledge is not attained solely by individual effort, but is partly revealed by God himself to persons suitably prepared.
The book has many functions, but chief among them must be counted the stress on the importance of the creation as a source of revelation as distinct from that of the Law. The book may also be seen as an elaborate polemic against contemporary creation myths and their protagonists. Job is a celebration of the belief that existence is ordered by a benevolent and knowable God and is not subject to the control of chaos. In that existence the filial relationship between the creator and the created is confirmed. The association of man with God in creation offers countless possibilities for wisdom. The same opportunities may not exist for a life circumscribed by the directives of the Law. In sum, the function of the creation motif in Job is to explore the significance of the divine-human relationship as it is revealed in creation.
The conclusion of this investigation is that the proper appreciation of the creation motif in Job makes tolerable sense of the whole work. Creation is important to Job because it provides him with a means of relating to God which was not possible under the Law. It follows that the poet has & higher regard for the usefulness of creation as a source of relation than for the Law itself. The notion of God's acting in history (Heilsgeschichte) also takes second place to his belief in the importance of creation. It is conceivable that the poet is emphasizing the revelatory content of creation at a time when other notions of the nature of God were in decline or disrepute. Alternatively, and more probably as far as Job is concerned, the post regarded creation as the supreme scenario in which revelation takes place.
Keywords: Religion; Religion